Neurotrophins as Therapeutic Agents for Parkinson’s Disease; New Chances From Focused Ultrasound? - Stefani, Alessandro; Pierantozzi, Mariangela; Cardarelli, Silvia; Stefani, Lucrezia; Cerroni, Rocco; Conti, Matteo; Garasto, Elena; Mercuri, Nicola B.; Marini, Carmine; Sucapane, Patrizia (Frontiers in Neuroscience, 2022)
Magnetic Resonance guided Focused UltraSound Surgery (MRgFUS) represents an effective micro-Magnetic Resonance guided Focused UltraSound (MRgFUS) represents an effective micro-lesioning approach to target pharmaco-resistant tremor, mostly in patients afflicted by essential tremor (ET) and/or Parkinson’s disease (PD). So far, experimental protocols are verifying the clinical extension to other facets of the movement disorder galaxy (i.e., internal pallidus for disabling dyskinesias). Asides from those neurosurgical options, one of the most intriguing opportunities of this technique relies on its capability to remedy the impermeability of blood brain barrier (BBB). Temporary BBB opening through low-intensity focused ultrasound (LIFU) turned out to be safe and feasible in patients with PD, Alzheimer’s disease and also Amiotrophic Lateral Sclerosis. As a mere consequence of the procedures, some groups described even reversible but significant mild cognitive amelioration, up to hippocampal neurogenesis partially associated to the increased of endogenous BDNF. A further development elevates FUS to the status of therapeutic tool for drug delivery of putative neurorestorative therapies. Since 2012, FUS-assisted intravenous administration of BDNF or Neurturin allowed hippocampal or striatal delivery. Experimental studies emphasized synergistic modalities. In a rodent model for Huntington’s disease (HD), engineered liposomes can carry GDNF plasmid DNA (GDNFp) to form a GDNFp-liposome (GDNFp-LPs) complex through pulsed FUS exposures with microbubbles; in a subacute MPTP-PD model, the combination of intravenous administration of neurotrophic factors (either through protein or gene delivery) plus FUS did curb nigrostriatal degeneration. Here we explore these arguments, focusing on the current, translational application of neurotrophins in neurodegenerative diseases.